Digital Culture: The Conception of Young Citizens - Apriyanda Kusuma Wijaya (International Journal of Education and Humanities, 2023)
This study aims to determine the conception of digital culture among young citizens. Digital culture is a citizen's ability to read, analyze, familiarize, examine, and form national insights, Pancasila values, ​​and diversity in social life. Indicators of this digital culture include understanding national culture (Pancasila and Bhineka Tunggal Ika), understanding the use of information and communication technology in culture, understanding how to love domestic products as part of defending the country, and having digital rights in which there is freedom and responsibility. This research departs from citizen communication patterns that have begun to transform into digital forms. This pattern has various impacts, both positive and negative. This pattern is then studied in the concept of digital citizenship. Digital citizenship requires moral principles to work effectively in a global society that is networked, multicultural across time and geographical areas. Citizenship requires balancing personal empowerment and responsibility with the well-being of society. The good of the individual and the good of society must be in balance. This research uses a type of quantitative approach with descriptive methods. This descriptive method is used to describe or analyze a research result but is not used to make broader conclusions. Respondents to this study were young citizens at the Tarbiyah and Teacher Training Faculty of IAIN Syekh Nurjati Cirebon who attended digital literacy outreach and filled out a questionnaire, totaling 105 respondents. Then the results of the research found that 25% really understood, and 48% understood. The percentage shows that students already understand digital culture well as young citizens.